INTEGRATION OF THE SECOND PRINCIPLE OF PANCASILA IN CIVIL LAW: A STUDY OF WAKALAH AGREEMENT IN MURABAHAH TRANSACTIONS AT ISLAMIC BANKS - Hermansyah; Melati, Prima; Maulana, Ana; Darojat, Arik; Dikarsa, Asep Anggi; Supriadi (Institut Pendidikan Indonesia, 2025)
This research is motivated by the importance of Pancasila values, particularly the second principle just and civilized humanity in the development and application of civil law in Indonesia. The aim of this study is to analyze the extent to which the humanitarian values embodied in the second principle of Pancasila are integrated into the practice of the wakalah contract in murabahah transactions at Islamic banks. This study employs a normative juridical approach with qualitative analysis of legislation, DSN-MUI fatwas, and Islamic banking practices. The findings indicate that the wakalah contract reflects humanitarian values through the principles of trust, responsibility, and contractual justice, which align with the core principles of national civil law. This integration demonstrates that the national legal system is capable of accommodating Pancasila values within the framework of Islamic economic law.